Clinical features and mutational frequency of renal cell carcinoma from patients undergoing kidney transplant evaluation - Eule, Corbin J.; Hu, Junxiao; Davies, Kurtis D.; Jani, Alkesh; Pshak, Thomas; Lam, Elaine T. (Frontiers in Oncology, 2025)
BackgroundPatients with chronic kidney disease (CKD) or post-kidney transplant have an elevated risk of renal cell carcinoma (RCC). Despite increased understanding of genomic alterations in clear cell and papillary RCC, the most common subtypes, little is known about the effects of renal dysfunction on RCC pathogenesis.Materials and methodsThis retrospective study analyzed electronic medical records and pathology data from adult patients with renal cell carcinoma (RCC) who were evaluated for or received a kidney transplant at a single institution between 1995 and 2021. Molecular sequencing of RCC tissue samples was conducted to compare mutation rates in patients with renal dysfunction compared with those reported by The Cancer Genome Atlas (TCGA).ResultsThis study identified 21 patients with RCC undergoing kidney transplant evaluation, mostly males with an increased occurrence of papillary RCC (38.1%) and early-stage disease (85.7%). Among clear cell RCC tumors, SDHA mutations were significantly more common compared to the TCGA cohort. For papillary RCC, genes such as BRD4 and those involved in DNA damage repair demonstrated increased mutation rates in patients with renal dysfunctionConclusionsThis study identifies key mutations in RCC among patients with CKD and post-kidney transplant, highlighting a complex relationship between renal dysfunction, inflammation, and tumorigenesis. Despite its limited sample size, the findings underscore the need for further research to understand the molecular drivers of RCC in high-risk populations, which could lead to more personalized treatment strategies.